2021
DOI: 10.1177/00031348211023397
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of Acetaminophen in Older Adult Trauma Patients

Abstract: Introduction Older adults are more vulnerable to opioid-associated morbidity. The purpose of this study was to determine the frequency and timing of acetaminophen and opioid use in the postoperative period. Methods Older adult trauma patients (≥65 years) with hip fractures requiring femur or hip fixation were reviewed (Premier Database 2008-2014). We examined rates of acetaminophen use on the day of surgery and prior to receipt of oral opioids. Mixed-effects linear regression models were used to examine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Our findings suggest that pain management and prevention of pain incidence and persistence may help mitigate cognitive decline. Safe regimens include cognitive-behavioral interventions and exercise (Williams et al, 2020) as well as safe medications like acetaminophen (Haines et al, 2021) among others. Improving pain management is a worthwhile goal as older adults are often unscreened (34%) and undertreated (40%) despite being the most affected by pain in the population (Herr & Titler, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that pain management and prevention of pain incidence and persistence may help mitigate cognitive decline. Safe regimens include cognitive-behavioral interventions and exercise (Williams et al, 2020) as well as safe medications like acetaminophen (Haines et al, 2021) among others. Improving pain management is a worthwhile goal as older adults are often unscreened (34%) and undertreated (40%) despite being the most affected by pain in the population (Herr & Titler, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We found this publication by Dr Haines et al 1 to be a pertinent and informative read. The authors reported on the efficacy of an "acetaminophen first" protocol, which was associated with reduced opioid use leading up to discharge in older adult trauma patients-a population with a steady increase in opioid-related deaths throughout the past 20 years.…”
mentioning
confidence: 79%
“…17 Previous studies have demonstrated that multimodal pain control significantly decreases the postoperative narcotic use in hip fracture surgery and provides more effective pain control. [18][19][20][21] While arthroplasty patients are also treated using this protocol, due to the higher incidence of preoperative narcotic use in this group, this model may be less effective in the elective arthroplasty patient population compared with the fracture population. Lastly, since elective THA patients presumably had higher preoperative pain due to chronic arthritis-related conditions, they would be expected to have less pain in the postoperative period than fracture patients.…”
Section: Discussionmentioning
confidence: 99%